Development of a Commercial Wet Wipe Sampling Method for the Collection of Methamphetamine Surface Residues for Forensic Analysis by Gas Chromatography-Mass Spectrometry (GC–MS) - เจริญกุลเมธี กชกร; ศุภลักษณ์นารี ศุภชัย; ชูสกุลเกรียง ศิริรัตน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to develop an alternative method for collecting methamphetamine residues from surfaces by utilizing commercial wet wipes as sampling materials. The study evaluated the feasibility of three distinct formulations—water-based, alcohol-based, and anti-bacterial—compared to the forensic standard protocols using methanol-soaked gauze and filter paper. Methamphetamine residues were prepared on laboratory bench surfaces (10 × 10 cm area). Samples were collected using a systematic cross-hatch pattern to minimize wiping direction variability, with each experiment performed in triplicate (n=3) to ensure result consistency. The acquired samples were extracted and qualitatively analyzed using Gas Chromatography–Mass Spectrometry (GC–MS). The results demonstrated a 100% detection rate for methamphetamine across all wet wipe formulations. Notably, the water-based wet wipe exhibited the highest performance, yielding a mean peak area of 60,826.58 and the lowest relative standard deviation (%RSD) at 15.27%, indicating a higher level of sampling consistency under the conditions of this study. These findings highlight the potential of commercial wet wipes as a convenient and non-destructive alternative for forensic evidence collection. Furthermore, conventional methods involving high volumes of organic solvents at crime scenes pose significant health risks to practitioners through hazardous chemical exposure. Therefore, the development of a wet wipe-based approach presents a highly effective and practical alternative. As a ready-to-use material, it simplifies field-based preparation and, most importantly, enhances the operational safety of forensic personnel.